2022
DOI: 10.1155/2022/2762582
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0000479/Hsa-miR-149-5p/RIG-I, IL-6 Axis: A Potential Novel Pathway to Regulate Immune Response against COVID-19

Abstract: Background. COVID-19, the disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has led to a global pandemic and mortality of people around the world. Some circular RNAs (circRNAs), one of the new types of noncoding RNAs (ncRNAs), act as competing endogenous RNAs (ceRNAs) and compete with mRNAs for shared miRNAs, to regulate gene expression. In the present study, we aimed to evaluate the expression and roles of hsa_circ_0000479/hsa-miR-149-5p/RIG-I, IL-6 in COVID-19 infection. Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…33 The regulatory effect of miR-1495p on the expression of IL-6 mRNA has been widely reported in various immune-mediated inflammatory diseases, including chronic obstructive pulmonary disease, COVID-19, abdominal aortic aneurysms, ischemic stroke, osteoarthritis and rheumatoid arthritis. [34][35][36][37][38] However, the regulatory relationship between ZBTB20-AS1 and miR-149-5p is only proposed based on database prediction and has not been supported in the current literature. Up-regulation of ZBTB20-AS1 and IL-6 and their targeting by miR-149-5p, combined with findings of related studies, indicate that the ZBTB20 − AS1/miR-149-5p/IL-6 axis may play a role in CSU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 The regulatory effect of miR-1495p on the expression of IL-6 mRNA has been widely reported in various immune-mediated inflammatory diseases, including chronic obstructive pulmonary disease, COVID-19, abdominal aortic aneurysms, ischemic stroke, osteoarthritis and rheumatoid arthritis. [34][35][36][37][38] However, the regulatory relationship between ZBTB20-AS1 and miR-149-5p is only proposed based on database prediction and has not been supported in the current literature. Up-regulation of ZBTB20-AS1 and IL-6 and their targeting by miR-149-5p, combined with findings of related studies, indicate that the ZBTB20 − AS1/miR-149-5p/IL-6 axis may play a role in CSU.…”
Section: Discussionmentioning
confidence: 99%
“…The miRNA is a noncoding RNA with a length of 19–25 nucleotides, which plays a role by blocking or degrading mRNA 33 . The regulatory effect of miR‐1495p on the expression of IL‐6 mRNA has been widely reported in various immune‐mediated inflammatory diseases, including chronic obstructive pulmonary disease, COVID‐19, abdominal aortic aneurysms, ischemic stroke, osteoarthritis and rheumatoid arthritis 34–38 . However, the regulatory relationship between ZBTB20‐AS1 and miR‐149‐5p is only proposed based on database prediction and has not been supported in the current literature.…”
Section: Discussionmentioning
confidence: 99%
“…Another study on chronic obstructive pulmonary disease reported that IL6‐AS1 (lncRNA) can competitively bind to miR‐149‐5p to promote the expression of IL‐6 33 . In addition, hsa_circ_0000479‐hsa‐miR‐149‐5p‐RIG‐I and IL‐6 interaction axis play a role in COVID‐19 infection 34 . Different circRNAs / lncRNAs can act on the hsa‐miR‐149‐5p‐IL‐6 axis.…”
Section: Discussionmentioning
confidence: 99%
“…33 In addition, hsa_circ_0000479-hsa-miR-149-5p-RIG-I and IL-6 interaction axis play a role in COVID-19 infection. 34 Different cir-cRNAs / lncRNAs can act on the hsa-miR-149-5p-IL-6 axis. Our network further suggested that the upregulated FTX, circRNA_7571, may be particularly important for AF due to their roles as ceRNA F I G U R E 8 Correlation of ceRNA expression levels with differential expression binding to hsa-miR-149-5p, which leads to the upregulation of IL-6, MMP9, respectively.…”
Section: Qrt-pcr and Correlation Analysis Of Differentially Expressed...mentioning
confidence: 99%
“…( 69 ) found that circRNAs composed of self-splicing introns can bind to the receptor retinoic acid-inducible gene I (RIG-I) to effectively activate immune signal transduction in the context of viral infection. A recent study also indicated that the overexpressed hsa_circ_0000479 in COVID-19 patients may regulate the expression of IL-6 and RIG-I by sponging hsa-miR-149-5p ( 55 ). Additionally, regulation of immune responses by circRNAs generally involves the transduction of signalling pathways and the production of cytokines.…”
Section: Potential Mechanisms Of Circrnas In Sars-cov-2 Infectionmentioning
confidence: 99%